Climate change vulnerability of Arctic char across Scandinavia - Clint C. Muhlfeld; Timothy J. Cline; Anders G. Finstad; Dag O. Hessen; Sam Perrin; Jens Thaulow; Diane Whited; Leif Asbjørn Vøllestad (Global Change Biology, 2024)
Climate change is anticipated to cause species to shift their ranges upward and poleward, yet space for tracking suitable habitat conditions may be limited for range‐restricted species at the highest elevations and latitudes of the globe. Consequently, range‐restricted species inhabiting Arctic freshwater ecosystems, where global warming is most pronounced, face the challenge of coping with changing abiotic and biotic conditions or risk extinction. Here, we use an extensive fish community and environmental dataset for 1762 lakes sampled across Scandinavia (mid‐1990s) to evaluate the climate vulnerability of Arctic char ( Salvelinus alpinus ), the world's most cold‐adapted and northernly distributed freshwater fish. Machine learning models show that abiotic and biotic factors strongly predict the occurrence of Arctic char across the region with an overall accuracy of 89 percent. Arctic char is less likely to occur in lakes with warm summer temperatures, high dissolved organic carbon levels (i.e., browning), and presence of northern pike ( Esox lucius ). Importantly, climate warming impacts are moderated by habitat (i.e., lake area) and amplified by the presence of competitors and/or predators (i.e., northern pike). Climate warming projections under the RCP8.5 emission scenario indicate that 81% of extant populations are at high risk of extirpation by 2080. Highly vulnerable populations occur across their range, particularly near the southern range limit and at lower elevations, with potential refugia found in some mountainous and coastal regions. Our findings highlight that range shifts may give way to range contractions for this cold‐water specialist, indicating the need for pro‐active conservation and mitigation efforts to avoid the loss of Arctic freshwater biodiversity.

Modelling temperature‐driven changes in species associations across freshwater communities - Sam Wenaas Perrin; Bert van der Veen; Nick Golding; Anders Gravbrøt Finstad (Global Change Biology, 2022)
Due to global climate change–induced shifts in species distributions, estimating changes in community composition through the use of Species Distribution Models has become a key management tool. Being able to determine how species associations change along environmental gradients is likely to be pivotal in exploring the magnitude of future changes in species’ distributions. This is particularly important in connectivity‐limited ecosystems, such as freshwater ecosystems, where increased human translocation is creating species associations over previously unseen environmental gradients. Here, we use a large‐scale presence–absence dataset of freshwater fish from lakes across the Fennoscandian region in a Joint Species Distribution Model, to measure the effect of temperature on species associations. We identified a trend of negative associations between species tolerant of cold waters and those tolerant of warmer waters, as well as positive associations between several more warm‐tolerant species, with these associations often shifting depending on local temperatures. Our results confirm that freshwater ecosystems can expect to see a large‐scale shift towards communities dominated by more warm‐tolerant species. While there remains much work to be done to predict exactly where and when local extinctions may take place, the model implemented provides a starting‐point for the exploration of climate‐driven community trends. This approach is especially informative in regards to determining which species associations are most central in shaping future community composition, and which areas are most vulnerable to local extinctions.